2023
DOI: 10.1165/rcmb.2022-0443oc
|View full text |Cite
|
Sign up to set email alerts
|

PFKFB3 Inhibits Fructose Metabolism in Pulmonary Microvascular Endothelial Cells

Abstract: Pulmonary microvascular endothelial cells contribute to the integrity of the lung gas exchange interface, and they are highly glycolytic. Although glucose and fructose represent discrete substrates available for glycolysis, pulmonary microvascular endothelial cells prefer glucose over fructose, and the mechanisms involved in this selection are unknown. 6-Phosphofructo-2-kinase/fructose-2, 6-bisphosphatase 3 (PFKFB3) is an important glycolytic enzyme that drives glycolytic flux against negative feedback and lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It has been shown that CA IX expression is higher and declines with extracellular acidity, which is related to cell proliferation, in pulmonary microvascular endothelial cells (PMVEs) compared with pulmonary arterial endothelial cells (PAECs). Moreover, CA IX is essential for PMVECs angiogenesis during acidosis by controlling the extracellular and intracellular pH (Lee et al, 2018). CA II has been identified as an antigen which elicited humoral immune responses in melanoma patients and expressed in the endothelium of new growth vessels in cancer tissues, including melanoma, and lung, renal and esophageal cancer (Yoshiura et al, 2005).…”
Section: The Function Of Ca In Vascular Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that CA IX expression is higher and declines with extracellular acidity, which is related to cell proliferation, in pulmonary microvascular endothelial cells (PMVEs) compared with pulmonary arterial endothelial cells (PAECs). Moreover, CA IX is essential for PMVECs angiogenesis during acidosis by controlling the extracellular and intracellular pH (Lee et al, 2018). CA II has been identified as an antigen which elicited humoral immune responses in melanoma patients and expressed in the endothelium of new growth vessels in cancer tissues, including melanoma, and lung, renal and esophageal cancer (Yoshiura et al, 2005).…”
Section: The Function Of Ca In Vascular Cellsmentioning
confidence: 99%
“…It is likely that these differences in EC morphology and function, and interactions with other vascular cells in the vascular wall of the vessels in question relate to the effectiveness of CA inhibitors as vasodilators in different vascular beds. Still, although CA II and CA IV have been shown to be expressed in the corneal endothelium (Nguyen and Bonanno, 2011), only the membrane bound CA IV and CA IX isoforms have been shown to be present in normal vascular endothelial cells, and not the CA II (Lee et al, 2018;Annan et al, 2019). However, CA II present in other vascular cells may have indirect effects on vascular endothelial function, but the structural and functional heterogeneity of ECs is likely to determine to what extent and by which mechanism CA is involved in regulation of vascular function in the organ concerned.…”
Section: Introductionmentioning
confidence: 98%